The exonuclease Xrn1 activates transcription and translation of mRNAs encoding membrane proteins - Bernat Blasco-Moreno (Nature Portfolio, 2019)
The exonuclease Xrn1 mediates crosstalk between transcription and mRNA decay in yeast. Here the authors demonstrate that Xrn1 promotes translation of mRNAs encoding membrane proteins, coupling transcription, translation, and mRNA decay.